Microbial carbon use efficiency and biomass turnover times depending on soil depth – Implications for carbon cycling. (May 2016) - Spohn, Marie; Klaus, Karoline; Wanek, Wolfgang; Richter, Andreas
Abstract: Processing of organic carbon (C) by soil microorganisms is a key process of terrestrial C cycling. For this reason we studied (i) microbial carbon use efficiency (CUE) defined as C allocated to growth over organic C taken up by the microbial community, and (ii) the turnover time of microbial biomass in a pasture and in two forest soils. We hypothesized that microbial CUE decreases in mineral soils with depth from the topsoil to the subsoil, while the turnover time of the microbial biomass increases due to energetic constrains. We determined microbial CUE and turnover of microbial biomass C using a novel substrate-independent method based on incorporation of 18 O from labeled water into microbial DNA with concurrent measurements of basal respiration. Microorganisms showed decreasing C uptake rates with decreasing C contents in the deeper soil layers. In the forest soils, no adaptation of microbial CUE with soil depth took place, i.e., microbes in the forest topsoil used C at the same efficiency as microbes in the subsoil. However, in the pasture soil, microbial CUE decreased in the lower soil layers compared to the topsoil, indicating that microorganisms in the deeper soil layers allocated relatively more C to respiration. In the organic soil layer, microorganisms respired more per unit microbial biomass C than in the subsoil, but had a similar CUE despite the high C-to-nitrogen and C-to-phosphorus ratios of the litter layers. The turnover time of microbial biomass increased with soil depth in the two forest soils. Thus, in the forest soils, a lower microbial C uptake rate in the deeper soil layers was partially compensated by a longer turnover time of microbial biomass C. In conclusion, our findings emphasize that in addition to microbial CUE, the turnover time of the microbial biomass strongly affects soil C cycling. Highlights: Microbial carbon use efficiency was determined by a substrate-independent method. Microbial carbon use efficiency hardly changed with soil depth in forest soils. Turnover time of the microbial biomass increased with soil depth. Microbial carbon uptake rates decreased with soil depth. Both microbial carbon use efficiency and biomass turnover affect carbon cycling.